. Serum levels of MMP3 could be used as a potential biomarker for sports induced knee osteoarthritis: Serum levels of MMP3 could be used as a potential biomarker - Yang, Xiaowei (Journal of Medical Biochemistry, 2025)
Aim:  Evaluating the serum concentrations of MMP3 may serve as a promising biomarker for the diagnosis of knee osteoarthritis caused by sports activities.Material and Methods: we identified 50 eligible participants for our research who had not had any other knee procedures apart from meniscus removal. For the determination of serum MMP-3 levels, blood was taken from 50 eligible individuals using 3 simple 6 mL EDTA vacutainer tubes. Patients also had knee aspirations, both surgical and non-surgical. Out of the 25 attempts, a successful knee synovial fluid aspirate was obtained. Additionally, all 25 attempts to get a contralateral control knee aspirate were successful. The raw values of the cohorts' demographics, radiological, clinical, PROMs, and biomarkers. Results: The duration of pain was 4.52±0.85 and 5.85±1.22 in non-operated and operated individuals, respectively. The VSA Pain score was 48.74±2.87 and 53.55±3.39, and the Lequesne algo functional index was 11.02±1.29 and 13.36±1.57 in non-operated and operated participants, respectively. We conducted a comparative analysis of MMP-3 and GAG levels in the knees of 25 patients who had successful bilateral knee synovial fluid aspirations, comparing the operated and non-operated knees. A comparative examination of MMP-3 levels in the synovial fluid shown that, despite the considerable time elapsed after the operation, the levels of MMP3 remain notably elevated in the operated knee (p = 0.01) .  Additionally, the levels of synovial GAGs in the operated joint were dramatically reduced (p = 0.03) . An inverse connection was seen between the levels of MMP-3 and GAGs in the synovial fluid when analysing all 50 samples from both operated and non-operated knees. The correlation coefficient (r) was -0.88, indicating a strong negative relationship. The p-value was 0.04, suggesting statistical significance.Conclusions: Our results suggest that MMP3 serum levels may be a simple blood test away from becoming a diagnostic tool for knee osteoarthritis and a possible predictor of the disease. To better assess athletes' joint health, it may be helpful to combine biomarkers with other diagnostic tools and have a comprehensive understanding of their athletic background.
Keywords: Serum, MMP3, Biomarker, Sports, Knee Osteoarthritis